Unveiling the potential of Garcinia atroviridis root-derived phenolic compounds against breast cancer: Isolation, network pharmacology and in-silico approaches - Nur Salsabila, Ahmad Roslan; Roney, Miah; Abdul Rashid, Issahaku; Md. Nazim, Uddin; Mohd Fadhlizil Fasihi, Mohd Aluwi; Seema, Zareen; Wilhelm, Anke; Ahmad Mahfuz, Gazali; Akhtar, Muhammad Nadeem; Normaiza, Zamri (Springer, 2025)
Purpose This study aimed to isolate and characterize bioactive compounds from the roots of Garcinia atroviridis and evaluate their potential anticancer activity, particularly against breast cancer (BC), through network pharmacology and in-silico approaches.